2023
DOI: 10.1063/5.0136002
|View full text |Cite
|
Sign up to set email alerts
|

Fourth-order stability analysis for capillary-gravity waves on finite-depth currents with constant vorticity

Abstract: We derive a fourth-order nonlinear evolution equation (NLEE) for narrow-banded Stokes wave in finite depth in the presence of surface tension and a mean flow with constant vorticity. The two-dimensional capillary-gravity wave motion on the surface of finite depth is considered here. The analysis is limited to one horizontal dimension, parallel to the direction of wave propagation, in order to take advantage of a formulation using potential flow theory. This evolution equation is then employed to examine the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Considering the significant influence of term on stability of wave modulation (Thomas et al. 2012; Francius & Kharif 2017; Dhar & Kirby 2023), wave kinematic and dynamic properties (Pizzo et al. 2023), and the geometry of the fluid particle trajectories (Wang, Guan & Vanden-Broeck 2020), we included this term in the present study.…”
Section: Mathematical Derivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the significant influence of term on stability of wave modulation (Thomas et al. 2012; Francius & Kharif 2017; Dhar & Kirby 2023), wave kinematic and dynamic properties (Pizzo et al. 2023), and the geometry of the fluid particle trajectories (Wang, Guan & Vanden-Broeck 2020), we included this term in the present study.…”
Section: Mathematical Derivationmentioning
confidence: 99%
“…The first-order problem is composed of waves propagating both forwards and backwards, as Mei (1985) demonstrated, and an additional non-propagative mode, B, which represents the wave-induced mean flow and is generated in the process of nonlinear wave modulations in slow spatial and time scales (Thomas et al 2012). Considering the significant influence of term B on stability of wave modulation (Thomas et al 2012;Francius & Kharif 2017;Dhar & Kirby 2023), wave kinematic and dynamic properties (Pizzo et al 2023), and the geometry of the fluid particle trajectories (Wang, Guan & Vanden-Broeck 2020), we included this term in the present study.…”
Section: First-order Problemmentioning
confidence: 99%
“…The new fourth-order outcome shows a remarkable modification in the instability behaviour from the third-order one in deep water. This paper is an extension of the paper by Dhar and Kirby [9] to include the effect of depth uniform current on modulational instability properties.…”
Section: Introductionmentioning
confidence: 98%
“…Hsu et al [16] then elaborated that paper to include capillarity, and studied both the effects of vorticity and capillarity on modulational instability. Later, Dhar and Kirby [9] derived a fourth-order nonlinear evolution equation (NLEE) for GCWs on finite depth with constant vorticity. From the studies on vorticity modified NLSEs of preceding authors, it is revealed that they considered only the effect of vorticity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the existence of stagnation points can generate flows where the pressure at the bottom boundary is out of phase with the free surface [11,12]. Many other authors have investigated waves with constant vorticity [11,13,14,15,16,17,18,19,20,21,22]. The readers are referred to the work by Nachbin and Ribeiro-Jr [23] for a review on numerical strategies adopted for capturing the flow beneath waves with constant vorticity.…”
Section: Introductionmentioning
confidence: 99%